A Damping Effect of the Maritime Continent for the Madden‐Julian Oscillation. Issue 24 (21st December 2019) - Jiang, Xianan; Su, Hui; Waliser, Duane E.
Abstract: The damping effect of the Maritime Continent (MC) on propagation of the Madden‐Julian Oscillation (MJO) has been widely recognized; however, its underlying physics remains largely elusive. Capitalizing on the latest high‐resolution reanalysis data (ERA‐5) from the ECMWF, analyses in this study suggest that the interruption of lower‐tropospheric moistening over the MC land during MJO eastward propagation is mainly due to a drying effect induced by zonal advection of the low‐level winter mean moisture by MJO winds. The low‐level mean moisture pattern over the MC tends to closely follow local topography, with moisture maxima collocated with local mountain peaks. Given this mean moisture distribution, the moisture advection by anomalous easterly MJO winds corresponding to the active MJO convection over the eastern Indian Ocean will lead to a drying (moistening) effect to the east (west) of the mountain peaks. Diagnosis based on hourly output from ERA‐5 further illustrates that the diurnal cycle plays a crucial role for the formation of the topographically locked mean moisture pattern over the MC. This study, therefore, indicates that high‐resolution models capable of resolving detailed topography and associated diurnal cycle over the MC could be necessary for realistic depiction of the interaction between the MC and MJO. Key Points: The MJO damping over the MC is linked to a drying effect due to advection of the topographically locked mean moisture by MJO winds The diurnal cycle plays a crucial role for the formation of the topographically locked mean moisture pattern over the MC High‐resolution models capable of resolving MC topography and diurnal cycle will be needed to represent interaction between the MC and MJO